Special interest (Nature (London), 2014)
Scientific leaders were presented front and centre as part of the dialogue, and both research and academic freedom in Scottish universities were held by both sides as a prize to value and fight for. Estimates of the size of the oil reserves in an independent Scotland became front- page news and even the subject of conspiracy theories, with allegations that the unionist UK government was concealing the true, vast scale of Scotland's potential future wealth.